Kolonoskopi sonrası abdominal masajın ağrı, distansiyon, hasta konforu ve memnuniyetine etkisi - Öztürk, Dilek (My University, 2023)
Amaç: Araştırmanın amacı kolonoskopi sonrası abdominal masajın ağrı, distansiyon, hasta konforu ve memnuniyetine etkisini belirlemektir. Gereç ve Yöntem: Randomize kontrollü türdeki çalışma, Kasım 2020-Mayıs 2021 tarihleri arasında bir şehir hastanesinin endoskopi ünitesinde ayakta sedasyonsuz kolonoskopi uygulanan 166 hasta ile gerçekleştirildi. Deney grubundaki hastalara (n=83) kolonoskopi günü (0. gün) işlemin bitiminde ve akşam, 1. gün sabah ve akşam olmak üzere 15 dakika abdominal masaj uygulandı. Kontrol grubuna (n=83) standart bakım ve tedavi dışında herhangi bir girişim uygulanmadı. Veriler Bireysel ve Klinik Özellikler Formu, Visual Analog Skala ve Hasta Takip Formları ile toplandı. Verilerin değerlendirilmesinde tanımlayıcı istatistikler, Independent Samples test, Mann-Whitney U test, Chi Square test, Wilcoxon Signed Rank testi kullanıldı. Bulgular: Katılımcıların yaş ortalaması 50,00±12,19 ve %51,2’si erkekti. Grupların bireysel ve klinik özellikleri ile çekal entübasyon ve toplam işlem süresi benzerdi (p>0,05). Deney grubu hastalarda abdominal masaj öncesine göre sonrası ağrı ve distansiyon puanlarının anlamlı olarak azaldığı ve konfor puanlarının arttığı saptandı (p<0,01). Kontrol grubuna göre de deney grubunun kolonoskopi günü işlemden 45 dakika sonra ve akşam, işlemin 1. günü sabah ve akşam abdominal ağrı ve distansiyon puanlarının anlamlı olarak daha düşük, abdominal konfor puanlarının daha yüksek olduğu bulundu (p<0,01). Ayrıca, kontrol grubuna göre deney grubunun işlemden memnuniyetinin de daha yüksek olduğu görüldü (p<0,01). Sonuç: Çalışma bulguları kolonoskopi sonrası uygulanan abdominal masajın abdominal ağrı ve distansiyonu azalttığı hasta konforu ve memnuniyetini artırdığını gösterdi.

Objective: The purpose of the study is to determine the effect of abdominal massage after colonoscopy on pain, distention, patient comfort and satisfaction. Material and Methods: This randomized controlled study was conducted with 166 patients who underwent outpatient colonoscopy without sedation in the endoscopy unit of a city hospital between November 2020 and May 2021. Patients in the experimental group (n=83) were administered abdominal massage for 15 minutes at the end of the colonoscopy (day 0) and in the evening, and on the first day in the morning and evening. No intervention was applied to the control group (n=83), other than standard care and treatment. Data were collected with Individual and Clinical Characteristics Form, Visual Analogue Scale and Patient Follow-up Forms. Descriptive statistics, Independent Samples test, Mann-Whitney U test, Chi Square test, Wilcoxon Signed Rank test were used to evaluate the data. Results: The mean age of the participants was 50.00±12.19 years and 51.2% were male. The individual and clinical characteristics of the groups, as well as the cecal intubation and total procedure time were similar (p>0.05). In the experimental group patients it was determined that abdominal pain and distension scores decreased significantly and comfort scores increased after the abdominal massage when compared with before (p<0.01). Compared to the control group, it was found that the abdominal pain and distension scores of the experimental group were significantly lower on the colonoscopy day 45 minutes after the procedure and in the evening, and on the first day of the procedure, in the morning and evening, and the abdominal comfort scores were higher (p<0.01). In addition, it was observed that the experimental group's satisfaction with the process was higher than the control group (p<0.01). Conclusion: The study findings showed that abdominal massage applied after colonoscopy decreased abdominal pain and distension and increased patient comfort and satisfaction.
The effect of post colonoscopy abdominal massage on pain, distension, patient comfort, and satisfaction
Keywords: Abdominal masaj; Abdominal massage; Ağrı; Colonoscopy; Distansiyon; Distension; Hasta memnuniyeti Colonoscopy; Kolonoskopi; Pain; Patient satisfaction